2019
DOI: 10.3390/cancers11091278
|View full text |Cite
|
Sign up to set email alerts
|

Increased Non-Homologous End Joining Makes DNA-PK a Promising Target for Therapeutic Intervention in Uveal Melanoma

Abstract: Uveal melanoma (UM) is the most common primary intraocular tumour in adults, with a mean survival of six months following metastasis. The survival rates have not improved in over 30 years. This study has shown that sister chromatid exchange (SCE) is low in UM which is likely due to a reduced expression of FANCD2. As FANCD2 can function to suppress non-homologous end joining (NHEJ), this study therefore investigated NHEJ in UM. The activation of the catalytic subunit of the NHEJ pathway protein DNA-dependent pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…Interestingly, in a recent study, greater gene expression of DNA-Pk was observed in metastatic UM, and was significantly associated with an adverse clinical outcome [ 13 ]. A second study also confirmed greater DNA-Pk expression in UM, although, similar to our study, no changes in ATM expression were observed [ 14 ]. This compares to recent data identifying loss of ATM and ATR in UM with a high risk of metastasis [ 15 , 16 ], although it should be noted that the goal of our study was not to determine whether specific DNA repair proteins are biomarkers of metastatic risk.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Interestingly, in a recent study, greater gene expression of DNA-Pk was observed in metastatic UM, and was significantly associated with an adverse clinical outcome [ 13 ]. A second study also confirmed greater DNA-Pk expression in UM, although, similar to our study, no changes in ATM expression were observed [ 14 ]. This compares to recent data identifying loss of ATM and ATR in UM with a high risk of metastasis [ 15 , 16 ], although it should be noted that the goal of our study was not to determine whether specific DNA repair proteins are biomarkers of metastatic risk.…”
Section: Discussionsupporting
confidence: 89%
“…We are aware that more potent and selective inhibitors targeting ATM, particularly AZD1390, are now available, and this will be the focus of our future studies, in combination with both photons and protons in enhancing the radiosensitivity of UM cell models. Interestingly, there are recent studies suggesting that the inhibition of another kinase involved in DSB repair, DNA-Pk, as a monotherapy can reduce the survival of UM cell lines [ 13 , 14 ]. There are also very limited data suggesting that DNA-Pk inhibition can work effectively in combination with X-rays in preventing UM cell survival [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…New targets for therapy are addressed by Rezzola et al who describe the fibroblast growth factors (FGFs) and their receptors as potential therapy targets in uveal melanoma and show the efficacy of FGF traps [22]. Doherty et al introduce the DNA-PK as a therapy target since its inhibition leads to increased non-homologous end joining and apoptosis [23]. Vivet-Noguer and colleagues review our knowledge of the molecular biology of uveal melanoma and how this might lead to the identification of new therapies [50].…”
mentioning
confidence: 99%